Interseccionalidade e imagologia nos poemas de Gessica Correia Borges - Guimarães, João Paulo Duque Löbe (2024)
This paper aims to analyse two poems by Gessica Correia Borges from the perspective of Imagology, highlighting that she is a feminist, Black author, and is herself the «Other» in the literary panorama in Portuguese. To achieve this purpose, we refer to the importance of symbolic power and male domination that still subjugates our society (Bourdieu 2002; Bourdieu 1989) and which conditions the literary production of Black women writers, and we highlight the issue of sex and gender issues, to make it more concise. As a theoretical complement, we consider it essential to address the concepts of Intersectionality, the subaltern condition, and Black feminism, given that this is a Black poet and activist who develops her activity in this movement and because these perspectives are essential for a comprehensive analysis. Finally, we point out the most important Imagology concepts, as this is the prism through which our approach will focus, and we propose our final considerations.